Preparation And Characterisation Of Hybrid Chitosan Films For The Mitigation Of Alexandrium Minutum - Ibrahim Syed Ali, Nur Hanisah (2022)
Harmful Algal Bloom (HAB) has been a growing issue worldwide for the past few decades, posing harm to aquatic ecosystems and drinking water quality. This phenomenon must be mitigated using a proper mitigation agent to reduce the negative impact. Herein, the research investigates the feasibility of a chitosan film (CH), hybrid chitosan/silica film (CH/SiO2) a with the addition of glycerol (CH/SiO2/gly) and (3-glycidyloxypropyl)trimethoxysilane (CH/SiO2/GPTEOS), and hybrid chitosan/TiO2 films were prepared via a one-pot synthesis method and characterised to mitigate toxic algae cells, Alexandrium minutum. The XRD pattern of the CH film confirms the peak related to the crystallographic planes (002), (101) and (220) of chitosan at 2θ= 10.1°, 19.8° and 22°, respectively. The XRD peaks appear broader after crosslinking with SiO2, glycerol and GPTEOS, indicating an increase in the polymer's amorphous nature, while the addition of TiO2 caused the peak of chitosan became weak and broaden after the incorporation. The films' TGA analysis shows that the film's weight loss reduces after the incorporation of SiO2, glycerol, GPTEOS and TiO2. In addition, the UV-vis spectra revealed that the films has an absorption innd at the UV region. All the films were subjected to the mitigation of Alexandium minutum. Among all the films, CH/0.2TiO2 (1 mL) gave a higher removal efficiency 76.1± 13.83 % at 72 hrs.